Banki spółdzielcze a Nowa umowa kapitałowa - Furtak, Bogdan (Cooperative banks and the new capital accord, 2006)
This paper presents origins and a general overview of the New Capital Accord. The recent developments of its implementation by Poland's cooperative banks are also highlighted.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1128, s. 29-34